Imagining the sacred past hagiography and power in early Normandy - Herrick, Samantha Kahn (Harvard historical studies ;, 2007)
"Investigating the role of religious traditions in the legitimate of power and the establishment of identity, Samantha Kahn Herrick illuminates the often murky early history of the duchy of Normandy. Central to this religious heritage stood the region's traditional saints, whose deeds, recorded in Latin lives, were celebrated regularly. Herrick focuses on the neglected figures Taurinus of Evreux, Vigor of Bayeux, and Nicasius of Rouen, saints with particular resonance in areas central to the Norman dukes' territorial ambitions. In elaborating a vision of the past that helped explain the present, the saints' stories sanctioned the dukes' rule." "Innovative in its historical use of hagiographical literature, this work advances our understanding of early Normandy and the Vikings' transformation from pagan raiders to Christian princes. It also sheds light on the intersection of religious tradition, identity, and power."--Jacket.